Biological Evaluation of Two 1,4-Naphthoquinone Derivatives Against a Breast Human Adenocarcinoma Cell Line - CREŢU, FLAVIA MARIA (Curr Health Sci J, 2017)
ABSTRACT: Two novel 1,4-naphthoquinone derivatives containing salicylic acid and procaine moieties were synthesized and evaluated for their anticancer activity in vitro. The antiproliferative effect was assayed against MDA-MB-231 cells, a human breast adenocarcinoma cell line, using CellTiter-Glo® Luminescent Cell Viability Assay. Both compounds tested proved a growth inhibition effect on this cell line in a dose-dependent manner. Our results showed that the compound with procaine effectively reduces breast cancer MDA-MB-231 cells viability and proliferation at higher concentration while that with salicylic acid had an inhibitory effect at lower concentrations and might be tested as an anticancer agent.